Synthesis and Characterization of Ni(II) Schiff Base Macrocyclic Complexes - Golbedaghi, Reza (Asian Journal of Chemistry, 2011)
[2+2]Cyclocondensation of L22py = N-(2-pyridylmethyl)-N-(2-aminoethyl)-1,2-diaminoethane, L23py = N-(2-pyridylmethyl)-N-(2-aminoethyl)-1,3-diaminopropane and 2-[3-(2-formyl phenoxy)propoxy]benzaldehye and 2-[4-(2-formyl phenoxy)butoxy]benzaldehyde in the presence of Ni(ClO4)2·4H2O in equimolar ratios gave three new binuclear Ni(II) macrocyclic complexes. Resulting compounds, [{Ni(H2L1)](ClO4)2 (1), [Ni(H2L2)](ClO4)2 (2) and [Ni(H2L3)](ClO4)2 (3), were characterized by IR spectroscopy and elemental analysis. The Ni(II) ions in latter complexes are six coordinated.